Karakterisasi Proses Gasifikasi Sampah Organik dengan Variasi Jenis Bahan - Ucik Ika Fenti Styana; Rosiana Indrawati; Muhammad Sigit Cahyono (Proklamasi 45 University, 2019)
One of the abundant energy source in Indonesia is organic waste in the form of leafs and branches which is widely avalilable in homeyard. It can be utilized as alternative energy source by gasification process. The objective of the study was to know the influence of raw material and AFR to the characteristic of organic waste gasification process. The raw material used were leafs and branches of melinjo (gnetum gnemon) which obtained from homeyard of inhabitant in Sidomoyo village, Godean sub-district, Sleman Regency, Indonesia. Before being gasified, it was prepared for proximate analysis in laboratorium. The gasification begins by feeding the raw material to the reactor with variation of 100% leaf, 100% branch, and 50%-50% leaf and branch. The gasification process was occured in reactor for one hour, and syn gas which produced has been analized to know the composition of it. Result shows that raw material have influenced the characteristic of gasification process. The highest heating rate was occured for gasification process of 100% leaf and AFR 0.5, which it gas has burned after 25 minuted process in oxidation temperature of 650 0C, reduction temperature of 350 0C, and pyrolysis temperature of 240 0C.